Leaching of copper from a flash furnace dust using sulfuric acid. (19th May 2022) - Ríos, G.; Ruiz, I.; Rius, O.; Cruells, M.; Roca, Antonio
ABSTRACT: Flash furnace dusts generated in copper pyrometallurgy are habitually recirculated to the furnace for copper recovery and as a cold burden material. However, it is necessary bled the dusts in order to reduce the amount of impurities to be recycled to the furnace. The most important processes for the treatment of Flash furnace dusts applied at the industrial scale are hydrometallurgical and mainly involve sulfuric acid. The objective of this work was to study the leaching of Flash furnace dusts generated in the Huelva, Spain, plant of Atlantic Copper using sulfuric acid. The work compares a leaching process developed in two steps, (first step with water, followed by leaching with sulfuric acid) to obtain a more selective leaching, or in a single step also with sulfuric acid, which decreases the operations number. A weak acid bleed ( wab ), from the same plant, was used as a source of sulfuric acid. After leaching, the concentration of sulfates and the acidity were reduced by gypsum precipitation. The liquids generated in this way are suitable for subsequent treatments of arsenic-iron precipitation and copper recovery by electrolysis.